STRATEGI PENGUATAN SUMBER DAYA MANUSIA DALAM MENDUKUNG PEMBANGUNAN HUKUM YANG BERKUALITAS DI INDONESIA - S.M, Probo Pribadi; Siburian, Risman Harianto; Saragih, Hotdesnan (Jurnal Hukum Statuta, 2025)
Human resources (HR) have a strategic role in legal development in Indonesia. Human resource development in Indonesia faces significant challenges, as seen from the ranking of 46 out of 67 countries in the International Institute for Management Development (IMD) World Talent Ranking (WTR) in 2024. This research uses a holistic normative juridical method with qualitative deductive analysis of primary, secondary, and tertiary data. The results showed that the quality of human resources in the legal sector has a significant influence on the effectiveness of law enforcement. The research concluded that a holistic approach is needed in strengthening legal human resources which includes increasing technical competence, moral integrity, and professionalism through continuing education, utilising technology, and building an organisational culture with integrity. The strengthening of quality human resources is expected to support the creation of a responsive legal system and provide substantive justice for all Indonesian people